Fiscal Expansion and External Current Account Balance. (IMF Working Papers; Working Paper ;, 1988)
This paper analyzes, in a general equilibrium framework, how fiscal policy transmits its effects to the current account of the balance of payments. In discussing the role of fiscal policies in the Fund's stabilization programs, the paper compares different approaches to explain the determination of the external balance. The model presented here is based on intertemporal optimization and focuses on the behavior of private and public agents. Some empirical evidence is also presented, based on data from ten Latin American countries. Finally, an appendix presents an integrated system of financial, external, and government accounts.